Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ags3.12646
|View full text |Cite
|
Sign up to set email alerts
|

Essential updates 2020/2021: Advancing precision medicine for comprehensive rectal cancer treatment

Abstract: In the paradigm shift related to rectal cancer treatment, we have to understand a variety of new emerging topics to provide appropriate treatment for individual patients as precision medicine. However, information on surgery, genomic medicine, and pharmacotherapy is highly specialized and subdivided, creating a barrier to achieving thorough knowledge. In this review, we summarize the perspective for rectal cancer treatment and management from the current standard‐of‐care to the latest findings to help optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 204 publications
(417 reference statements)
0
6
0
Order By: Relevance
“…1,2 Preoperative radiotherapy (RT) has been the main approach for LARC around the world, but its ineffectiveness in reducing systemic recurrence and radiation-induced late toxicity has led to the desire for the development of effective radiation-independent treatments. 3,4 In this context, it has been reported that multi-agent chemotherapy and molecular-targeted agents for unresectable colorectal cancer are effective not only for metastatic disease but also for primary lesions, and that radiotherapy may be avoided in LARC. 5,6 On the other hand, in past reports, the pathologic response rate (pCR) with neoadjuvant chemotherapy (NAC) alone was not high (4.3%-13.3%) for high-risk LARC, with bevacizumab contributing to a high incidence of anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Preoperative radiotherapy (RT) has been the main approach for LARC around the world, but its ineffectiveness in reducing systemic recurrence and radiation-induced late toxicity has led to the desire for the development of effective radiation-independent treatments. 3,4 In this context, it has been reported that multi-agent chemotherapy and molecular-targeted agents for unresectable colorectal cancer are effective not only for metastatic disease but also for primary lesions, and that radiotherapy may be avoided in LARC. 5,6 On the other hand, in past reports, the pathologic response rate (pCR) with neoadjuvant chemotherapy (NAC) alone was not high (4.3%-13.3%) for high-risk LARC, with bevacizumab contributing to a high incidence of anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that extended surgery alone results in a high rate of recurrence, with about half of affected patients dying of cancer 1,2 . Preoperative radiotherapy (RT) has been the main approach for LARC around the world, but its ineffectiveness in reducing systemic recurrence and radiation‐induced late toxicity has led to the desire for the development of effective radiation‐independent treatments 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…However, while such novel organ-preserving strategies offer numerous advantages over traditional surgery, there is a crucial knowledge gap in the treatment response assessment pertaining to these strategies. Of several modern imaging techniques, rectal magnetic resonance imaging (MRI) is promising for the purpose of treatment response assessment, but to date, the literature remains lacking concerning its use in the post-neoadjuvant therapy setting in patients with rectal cancer [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 20,000 patients undergo surgery for rectal cancer annually in Japan 1 . The gold standard treatment for resectable lower rectal cancer is total mesorectal excision (TME) 2,3 . However, more extensive surgery is required in patients with lateral lymph node metastases.…”
mentioning
confidence: 99%